Dual-Pumped Degenerate Optical Parametric Oscillator in a Silicon Nitride Microresonator - Okawachi, Yoshitomo; Yu, Mengjie; Luke, Kevin; Carvalho, Daniel O. [UNESP]; Farsil, Alessandro; Ramelow, Sven; Lipson, Michal; Gaeta, Alexander L.; IEEE (Ieee, 2016)
We demonstrate frequency-degenerate optical parametric oscillation via four-wave mixing using dual pumps in a silicon-nitride microresonator. The system offers potential for realization of coherent optical computing and all-optical quantum random number generation.